Plastic optical fiber and method for manufacturing the same, and plastic optical fiber cord using the same

By increasing the birefringence Δn in the outer covering part of the plastic optical fiber, and using a polycarbonate resin and a low stretch ratio manufacturing method, the problem of easy cracks in the external force state of plastic optical fiber is solved, and a higher solvent crack resistance and service life are achieved.

CN113811801BActive Publication Date: 2025-04-01NITTO DENKO CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202080035317.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-05-13
Filing Date
2020-04-27
Publication Date
2025-04-01
Estimated Expiration
2040-04-27

AI Technical Summary

Technical Problem

Existing plastic optical fibers are prone to cracks when used for a long time when external force is applied.

Method used

By increasing the birefringence Δn to 0.002 or more in the outer covering portion of the plastic optical fiber, specifically, by using a polycarbonate resin as the material of the outer covering portion, and performing a stretching treatment with a low stretch ratio during the manufacturing process, the molecular orientation state of the outer covering portion is improved.

Benefits of technology

A plastic optical fiber that can suppress cracks even when an external force is applied is realized, which improves resistance to fiber bundler and extends the service life of the optical fiber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113811801B_ABST
    Figure CN113811801B_ABST
Patent Text Reader

Abstract

The present invention provides a plastic optical fiber that is crack-free even when used for a long time under an external force. The plastic optical fiber (10) of the present invention comprises a core (12), a cladding (14) arranged on the periphery of the core (12), and an outer cladding (16) arranged on the periphery of the cladding (14), and the birefringence Δn of the outer cladding (16) is greater than 0.002.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a plastic optical fiber and a manufacturing method thereof, and a plastic optical fiber soft wire using the plastic optical fiber. Background Art

[0002] As a light transmission medium, plastic optical fiber (hereinafter sometimes referred to as POF), whose core and cladding are both made of plastic, has attracted much attention. POF is a composite material with a tensile body and coated with a soft polyvinyl chloride (PVC) resin, etc., and is laid and used in the form of a cord or cable. However, if POF is used for a long time in a state where an external force is applied in the diameter direction of the cross section perpendicular to the longitudinal direction (for example, in a bent state, or in a state where it is tightly bundled with other wires when it is cabled), cracks may occur.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 5-11128

[0006] Patent Document 2: Japanese Patent Application Publication No. 2000-147272

[0007] Patent Document 3: International Publication No. 2004 / 102243

[0008] Patent Document 4: Japanese Patent Application Publication No. 2005-326502

[0009] Patent Document 5: Japanese Patent Application Publication No. 2007-199420

[0010] Patent Document 6: Japanese Patent Application Publication No. 2011-232726 Summary of the invention

[0011] Problems to be solved by the invention

[0012] The present invention has been made to solve the above-mentioned conventional problems, and a main object of the present invention is to provide a plastic optical fiber in which cracks are suppressed even when used for a long period of time with an external force applied thereto.

[0013] Means for solving problems

[0014] The plastic optical fiber of the present invention comprises a core, a cladding arranged on the periphery of the core, and an outer cladding arranged on the periphery of the cladding, wherein the birefringence Δn of the outer cladding is not less than 0.002.

[0015] In one embodiment, the outer covering portion includes a polycarbonate-based resin.

[0016] In one embodiment, the plastic optical fiber is bent with a curvature radius of 20 mm and left in contact with polyethylene glycol or a long-chain aliphatic hydrocarbon for one week without generating cracks.

[0017] According to another aspect of the present invention, a method for manufacturing the plastic optical fiber includes forming a preform and stretching the preform, wherein the stretching ratio is less than 1.2 times and the stretching temperature is lower than the glass transition temperature of the outer coating.

[0018] According to another aspect of the present invention, a plastic optical fiber cord is provided, which comprises the above-mentioned plastic optical fiber.

[0019] Effects of the Invention

[0020] According to the present invention, by controlling the orientation state of the outer coating covering the coating in the plastic optical fiber to set the birefringence Δn to a predetermined value or more, a plastic optical fiber can be realized in which cracks are suppressed even when used for a long time with external force applied. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic cross-sectional view taken along a plane perpendicular to the longitudinal direction of a plastic optical fiber according to an embodiment of the present invention.

[0022] Figure 2 This is a schematic cross-sectional view of a plastic optical fiber cord according to an embodiment of the present invention, taken along a plane perpendicular to the longitudinal direction. DETAILED DESCRIPTION

[0023] Embodiments of the present invention will be described below, but the present invention is not limited to these embodiments.

[0024] A. Plastic optical fiber

[0025] A-1. Overview of Plastic Optical Fiber

[0026] Figure 1 It is a schematic cross-sectional view of a plane perpendicular to the length direction of a plastic optical fiber according to an embodiment of the present invention. The plastic optical fiber (POF) 10 shown in the figure has: a core 12, a cladding 14 arranged on the periphery of the core 12, and an outer cladding 16 arranged on the periphery of the cladding 14. Typically, the cladding 14 covers the entire periphery of the core 12, and the outer cladding 16 covers the entire periphery of the cladding 14. The POF can be a step index type (SI type) or a graded index type (GI type). In addition, the POF can be multimode or single mode.

[0027] In an embodiment of the present invention, the birefringence Δn of the outer coating 16 is greater than or equal to 0.002. By setting the birefringence Δn of the outer coating to greater than or equal to 0.002, a plastic optical fiber can be realized in which cracks are suppressed even when used for a long time under the application of external force. More details are as follows. Typically, POF is compounded with a fiber tensile body (e.g., aromatic polyamide fiber) and coated with a soft PVC resin or the like, and used in the form of a soft wire or cable. Here, the fiber tensile body contains a fiber sizing agent, and there are cases where cracks are generated in the outer coating due to the influence of the fiber sizing agent. Typically, cracks are generated due to long-term use, and are particularly prominent in locations where external force is applied in the diameter direction (e.g., bends, and portions tightly bundled with other wires when cabled). Representative examples of fiber sizing agents include polyethers (e.g., polyethylene glycol) and long-chain aliphatic hydrocarbons. By increasing the molecular orientation of the outer covering (the material constituting it) in the fiber length direction until the birefringence Δn of the outer covering becomes 0.002 or more, the resistance to the fiber sizing agent can be improved, and as a result, cracks can be suppressed (hereinafter, this characteristic is sometimes referred to as solvent crack resistance). In particular, cracks can be well suppressed even when used for a long time under the condition of applying external force. Although the theory is not clear, it is speculated that the reason is as follows: it is believed that when stress acts on POF, the oil components such as the above-mentioned fiber sizing agent contact the POF and are absorbed by the POF surface, and cracks become easy to generate in the cross-sectional direction of the POF. Thereafter, the oil components enter and the cracks develop in the cross-sectional direction of the POF. By increasing the molecular orientation of the outer covering in the length direction of the POF, the generation of cracks in the cross-sectional direction of the POF is suppressed, and even if small cracks are generated, the molecular chains of the material constituting the outer covering are oriented in a direction orthogonal to the direction of crack development, so the development of the cracks can be suppressed. Similarly, there is a case where the plasticizer (e.g., tri(2-ethylhexyl) trimellitate) contained in the soft PVC resin of the coating material moves from the gap of the fiber tensile body and contacts the POF to cause cracks, but even in this case, cracks can be suppressed. It should be noted that regarding the birefringence Δn, the in-plane phase difference Δnd of the outer coating portion can be derived by the peak-to-valley method, and the phase difference Δnd can be divided by the thickness D of the outer coating portion. OC And obtain.

[0028] In one embodiment, the POF does not produce cracks after being bent with a radius of curvature of 20 mm and placed in contact with polyethylene glycol or long-chain aliphatic hydrocarbons for 1 week. As described above, this solvent crack resistance can be achieved by increasing the molecular orientation state of the fiber length direction of the outer coating (the material constituting it) until the birefringence Δn of the outer coating becomes 0.002 or more. The curvature radius of the bend is as described above, preferably less than 20 mm, more preferably less than 15 mm, and further preferably less than 10 mm. The lower limit of the radius of curvature can be, for example, 3 mm. The longer the time without cracks, the better. The specific example of this time is as described above, preferably more than 1 week, more preferably more than 2 weeks, and further preferably more than 1 month. According to an embodiment of the present invention, a POF that does not produce cracks even after such a long time can be actually obtained. The substance in contact with the POF is representatively a substance that can be used as a fiber sizing agent. As a specific example of such a substance, in addition to the above-mentioned polyethylene glycol and long-chain aliphatic hydrocarbons, water-soluble epoxy resins, imidazole silane compounds, and unsaturated carboxylic acid esters can also be listed. In this specification, "long-chain aliphatic hydrocarbon" refers to an aliphatic hydrocarbon having 12 or more carbon atoms. In addition, in this specification, "long-chain aliphatic hydrocarbon" also includes long-chain aliphatic hydrocarbon esters of carboxylic acids. Specific examples of long-chain aliphatic hydrocarbons are described in Japanese Patent Publication No. 2009-74229 and Japanese Patent Publication No. 11-335972. The records in these publications are cited in this specification as reference. As a representative example of long-chain aliphatic hydrocarbons, diisononyl phthalate can be cited.

[0029] Hereinafter, the constituent elements of POF will be described in detail.

[0030] A-2. Core

[0031] The core 12 may include any suitable material. Typically, the core includes an acrylic resin. In one embodiment, the core includes an acrylic resin containing trichloroethyl methacrylate (hereinafter sometimes referred to as TCEMA) as the main component of the monomer component. In this case, the acrylic resin can be obtained by polymerizing monomer components including TCEMA and methyl methacrylate (hereinafter sometimes referred to as MMA), methyl acrylate (hereinafter sometimes referred to as MA), N-cyclohexylmaleimide (hereinafter sometimes referred to as N-cHMI), cyclohexyl acrylate (hereinafter sometimes referred to as cHA), trichloroethyl acrylate (hereinafter sometimes referred to as TCEA), isobornyl acrylate (hereinafter sometimes referred to as iBoA) and / or cyclohexyl methacrylate (hereinafter sometimes referred to as cHMA) as copolymer components. Here, "main component" refers to the component with the largest weight in the monomer component. TCEMA can be preferably contained in the monomer component in a ratio of 70% by weight or more, more preferably 80% by weight to 100% by weight. TCEMA can also be contained in the monomer component in a ratio of 80% by weight to 95% by weight. By using TCEMA in a ratio of 70% by weight or more in the monomer components, it is possible to form a core portion having excellent transparency and capable of increasing a communication distance.

[0032] The core 12 is formed of the acrylic resin as a main component. Here, "main component" refers to the component with the largest weight among all components constituting the core, and means that other resins, dopants described later, additives, etc. may be included in addition to the main component.

[0033] The core 12 preferably contains a dopant. By containing a dopant, a gradient refractive index can be given to the core. That is, a GI-type POF can be obtained. By giving a gradient refractive index to the core, the communication speed can be improved. In order to give a gradient refractive index, it is useful to adjust the concentration distribution of the dopant in the core. The dopant preferably has compatibility with the main constituent of the core, namely the acrylic resin, and is a compound with a refractive index different from that of the acrylic resin. By using a compound with good compatibility, turbidity of the core can be avoided, scattering loss can be suppressed as much as possible, and the communication distance can be increased. Representative examples of dopants with a high refractive index include: diphenyl sulfone (DPSO) and diphenyl sulfone derivatives (for example: chlorinated diphenyl sulfones such as 4,4′-dichlorodiphenyl sulfone, 3,3′,4,4′-tetrachlorodiphenyl sulfone), diphenyl sulfide (DPS), diphenyl sulfoxide, dibenzothiophene, dithiane derivatives and other sulfur compounds; triphenyl phosphate (TPP), tricresyl phosphate and other phosphoric acid compounds; benzyl benzoate; benzyl n-butyl phthalate; diphenyl phthalate; biphenyl; diphenylmethane, etc. Representative examples of dopants with a low refractive index include tri(2-ethylhexyl) phosphate (TOP), etc. These can be used alone or in combination of two or more. DPSO, DPS, TPP, TOP are preferred. These can maintain the transparency and heat resistance of the core and can increase the communication speed. DPS, TPP, TOP are more preferred. DPS has the effect of suppressing the thermal decomposition of an acrylic resin having TCEMA as a main component (main structural unit), and TPP and TOP can capture hydrochloric acid released due to heat load.

[0034] The content of the dopant in the core can be appropriately set according to the required structure of the POF, the constituent material of the core and the required refractive index, the constituent material of the cladding and the required refractive index, etc. The content of the dopant can be, for example, 0.1 to 25 parts by weight, for example, 1 to 20 parts by weight, and for example, 2 to 15 parts by weight relative to 100 parts by weight of the constituent material of the core.

[0035] Details of the acrylic resin and dopant constituting the core are described in Japanese Patent Application Laid-Open No. 2011-232726, and the description of this publication is incorporated herein by reference.

[0036] The refractive index of the core is N CO It is preferably 1.3 to 1.7, and more preferably 1.4 to 1.6. When the refractive index of the core is within such a range, it is easy to set the difference in refractive index with the cladding to an appropriate value.

[0037] Core diameter D COIt is preferably 10 μm to 2000 μm, and more preferably 30 μm to 1000 μm. If the core diameter is within such a range, there is an advantage that the degree of freedom in positional alignment when connecting a light source to the POF is large.

[0038] A-3. Coating

[0039] The coating 14 may include any appropriate material. Typically, the coating includes an acrylic resin. In one embodiment, the coating includes an acrylic resin containing MMA as a monomer component. In this case, the acrylic resin can be obtained by polymerizing a monomer component containing MMA and TCEMA, MA, N-cHMI, cHA, TCEA, iBoA and / or cHMA as a copolymer component. MMA may preferably be contained in the monomer component in a ratio of 20% by weight or more, more preferably 30% by weight to 100% by weight. MMA may also be contained in the monomer component in a ratio of 30% by weight to 95% by weight. By using MMA in a ratio of 20% by weight or more in the monomer component, a coating having excellent flexibility and a refractive index moderately smaller than that of the core can be formed. As a result, the bending loss of the POF can be suppressed and the communication speed can be improved.

[0040] The cladding 14 may also contain a dopant. The dopant is as described in Item A-2 related to the core. When the cladding contains a dopant, its content can be appropriately set according to the required structure of the POF, the constituent material of the cladding and the required refractive index, and the constituent material of the core and the required refractive index. The content of the dopant can be, for example, 0 to 25 parts by weight, for example, 0 to 20 parts by weight, and for example, 0 to 15 parts by weight relative to 100 parts by weight of the constituent material of the cladding.

[0041] Details of the acrylic resin and dopant constituting the coating are described in Japanese Patent Application Laid-Open No. 2011-232726, the contents of which are incorporated herein by reference.

[0042] Typically, the refractive index N of the cladding is CL Smaller than the refractive index N of the core CO The refractive index of the cladding is N CL The refractive index N of the core CO The difference (N CO -N CL ) is preferably greater than 0.002, more preferably greater than 0.005. The upper limit of the difference may be, for example, 0.02. If the difference is within this range, it has the advantage of reducing light leakage from the core to the outside of the cladding during light transmission.

[0043] The thickness D of the covering portion 14 CLIt is preferably 2 μm to 300 μm, and more preferably 5 μm to 250 μm. If the thickness of the cladding is within this range, the light used for communication can be well sealed in the core, so a POF with excellent light transmission efficiency can be realized. In addition, the POF itself can be made thinner, which is also advantageous from the perspective of bendability and light weight.

[0044] A-4. Outer covering

[0045] As described above, the birefringence Δn of the outer coating 16 is greater than 0.002, preferably greater than 0.003, more preferably greater than 0.004, and further preferably greater than 0.005. The upper limit of the birefringence Δn of the outer coating 16 can be, for example, 0.020. By setting the birefringence of the outer coating to this range, excellent solvent crack resistance can be achieved as described above. In addition, by setting the upper limit of the birefringence to the above range, the breakage of the core and the coating can be well suppressed. This birefringence can be achieved by improving the molecular orientation state of the outer coating (the material constituting it) in the fiber length direction. Specifically, this outer coating can be formed by performing a specific stretching treatment as described in item B described later.

[0046] The outer coating 16 may include any appropriate material as long as it can show the birefringence as described above. Preferably, the outer coating may include a material having excellent mechanical properties and excellent adhesion to the coating in addition to the birefringence as described above. As a specific example of such a material, a polycarbonate resin can be cited. By using a polycarbonate resin to constitute the outer coating, a POF having excellent transparency, heat resistance and flexibility can be achieved. The polycarbonate resin is preferably a modified polycarbonate resin compounded with a polyester. The reason is that such a resin has excellent chemical resistance and fluidity.

[0047] The thickness D of the outer covering portion 16 OC It is preferably 50 μm to 500 μm, and more preferably 70 μm to 300 μm. When the thickness of the outer coating is within this range, the core and the coating can be well protected, and the flexibility and softness required of POF can be satisfied.

[0048] B. Manufacturing method of plastic optical fiber

[0049] The POF described in the above item A can be produced, for example, by forming a preform in advance and then stretching the preform. In this specification, the "preform" is an unstretched POF having a core, a cladding and an outer cladding. The preform can be obtained by any appropriate method. Representative examples of methods for producing preforms include: melt extrusion, melt spinning, melt extrusion dopant diffusion (Japanese: melt extrusion dopant diffusion method), and sleeve method. In these methods, steps well known in the industry can be used. For example, according to the melt extrusion method, the material constituting the core, the material constituting the cladding and the material constituting the outer cladding are respectively supplied to concentric 3-layer molds, and melt extruded at a specified temperature, thereby producing a preform having the following characteristics: Figure 1 In addition, for example, according to another melt extrusion method, the material constituting the core part and the material constituting the covering part are respectively supplied to a concentric double-layer die, and melt-extruded at a predetermined temperature, and another double-layer die is further used to make the melt-extruded material constituting the outer covering part merge outside the flow path of the core part and the covering part melt, thereby, a preform having a cross-sectional structure can be produced. Figure 1 The preform having such a cross-sectional structure. In the melt spinning method, a spinning nozzle (typically a three-layer nozzle) is used instead of a die.

[0050] Next, the obtained preform is cooled to a predetermined temperature without substantially stretching it. Cooling can be carried out using any appropriate cooling means, or it can be cooled naturally (let to cool). The predetermined temperature is preferably lower than the glass transition temperature (Tg) of the outer covering, more preferably (Tg-60°C) to (Tg-10°C), and further preferably (Tg-50°C) to (Tg-20°C). It should be noted that there is a situation where, by appropriately adjusting the constituent materials of the core, covering and outer covering, as well as the stretching ratio and stretching speed, an outer covering having the desired birefringence Δn can be formed even when the stretching temperature exceeds the Tg of the outer covering.

[0051] Next, the preform is stretched at the specified temperature. Generally, it is substantially difficult to stretch at a temperature lower than Tg, but according to an embodiment of the present invention, by appropriately selecting the constituent materials of the core, the cladding, and the outer cladding (i.e., the Tg of the core, the cladding, and the outer cladding) and adjusting the stretching speed described later, it can be stretched to about 1.2 times. Moreover, by stretching at such a low stretching ratio, the orientation state of the outer cladding can be significantly improved (the result is the birefringence Δn). This is an excellent effect beyond expectations that cannot be imagined based on the technical common sense in the industry of polymer processing. As a result, a POF with excellent solvent crack resistance can be obtained.

[0052] Typically, the stretching ratio is 1.2 times or less as described above, preferably 1.02 times to 1.18 times, more preferably 1.05 times to 1.15 times, and further preferably 1.08 times to 1.12 times. According to an embodiment of the present invention, by appropriately combining the constituent materials of the core, the cladding and the outer cladding, the stretching temperature and the stretching speed described later, the orientation state of the outer cladding (resulting in birefringence Δn) can be significantly improved even at such a low stretching ratio. As a result, a POF with excellent solvent crack resistance can be obtained. It should be noted that there is a situation where, by appropriately adjusting the constituent materials of the core, the cladding and the outer cladding and the stretching temperature, an outer cladding having the desired birefringence Δn can be formed even when the stretching ratio exceeds 1.2 times. Alternatively, by stretching when the preform is formed, without stretching the preform that has been formed, an outer cladding having the desired birefringence Δn can be formed. Specifically, the outer covering portion having the desired birefringence Δn can be formed by stretching the molten filaments extruded with a large diameter to the desired diameter while melt spinning. In this case, the stretching of the preform that has been formed can be omitted. In addition, the stretching ratio of the extruded molten filaments becomes very large. For example, when the extrusion diameter at the time of melting is 10 mm and the diameter of the preform to be formed is 400 μm, the stretching ratio of the extruded molten filaments becomes 625 times.

[0053] The stretching speed is preferably 0.05 m / min to 0.20 m / min, more preferably 0.07 m / min to 0.15 m / min, and further preferably 0.08 m / min to 0.12 m / min. At this stretching speed, the desired stretching as described above can be achieved. This stretching speed is extremely low compared to normal. By combining this low stretching speed with the stretching temperature less than Tg as described above, a POF including an outer cladding having a desired birefringence Δn can be manufactured without breaking the preform.

[0054] POF can be produced in the above manner. It should be noted that a series of operations from forming a preform to stretching can be performed continuously, or a preform that has been temporarily stored can be subjected to stretching.

[0055] C. Plastic optical fiber cord

[0056] The POF described in the above items A and B can be used for plastic optical fiber cords. Therefore, the embodiments of the present invention also include plastic optical fiber cords. Figure 2This is a schematic cross-sectional view of a plane perpendicular to the longitudinal direction of a plastic optical fiber cord (hereinafter sometimes referred to as a POF cord) according to an embodiment of the present invention. The POF cord 100 shown in the figure has one or more (two in the example shown) POFs 10, a fiber tensile member 20 arranged to surround the outer periphery of the POF 10, and a coating 30 that coats the fiber tensile member 20. The POF is the POF described in the above-mentioned items A and B.

[0057] Examples of the fibers constituting the fiber tensile member 20 include aramid fibers, polyethylene terephthalate (PET) fibers, carbon fibers, and glass fibers. Aramid fibers are preferred because they are excellent in rigidity, flexibility, and resistance to fracture due to repeated bending. The fibers constituting the fiber tensile member preferably have a cord modulus of 100 GPa or more as measured by ASTM-D885M.

[0058] The covering portion 30 typically contains a resin that is chemically stable to the fiber sizing agent. Examples of the resin include soft PVC resin, acrylic resin, silicone resin, silicone sealant, and epoxy resin. The thickness of the covering portion can be, for example, 10 μm to 50 μm.

[0059] Example

[0060] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. It should be noted that the measuring methods of the various properties are as follows.

[0061] (1) Birefringence Δn of the outer cladding

[0062] The POF obtained in the embodiment and the comparative example is sandwiched between two glass slides, and the gap is filled with matching oil having the same refractive index as the outer coating, and the one obtained in this way is used as a sample. A pair of analyzers (Japanese: shuttle photon) is prepared and arranged in the form of analyzer / sample / analyzer. At this time, the pair of analyzers are arranged in an orthogonal Nicol state, and the optical axis of the analyzer is arranged at 45° relative to the length direction of the POF. In this state, a microspectrophotometer (manufactured by Craic Technologies, product name "308PV") is used to measure the spectral transmittance of the portion of the outer coating near the center of the POF from above the sample. The in-plane phase difference value Δnd of the outer coating is derived from the wavelengths of the peaks and valleys of the spectral spectrum (peak-valley method). The obtained in-plane phase difference value Δnd is divided by the thickness D of the outer coating. OC The birefringence Δn of the outer cladding portion is calculated.

[0063] (2) Solvent crack resistance

[0064] The POF obtained in the examples and comparative examples was bent with a curvature radius of 20 mm and fixed at both ends. Diisononyl phthalate (DINP) was dropped into the bent portion, and the time until cracks occurred was measured while maintaining the presence of DINP in the bent portion.

[0065] <Example 1>

[0066] The purified TCEMA was mixed with DPS as a dopant at a weight ratio of TCEMA:DPS=100:4. Furthermore, di-tert-butyl peroxide as a polymerization initiator and n-lauryl mercaptan as a chain transfer agent were added in such a manner that the concentrations in the total weight were 0.03 wt% and 0.2 wt%, respectively. Thereafter, the mixture was filtered through a membrane filter with a pore size of 0.2 μm. The mixture was degassed under reduced pressure while applying ultrasonic waves, and then placed in a polymerization container. The temperature of the polymerization container was maintained at 120°C, and the monomers were polymerized for 40 hours to obtain a core rod (outer diameter 30 mm).

[0067] On the other hand, the purified TCEMA and MMA were mixed at a weight ratio of TCEMA:MMA=20:80. Further, benzoyl peroxide as a polymerization initiator and n-butyl mercaptan as a chain transfer agent were added in such a manner that the concentrations in the total weight were 0.5% by weight and 0.3% by weight, respectively. Thereafter, the mixture was filtered through a membrane filter having a pore size of 0.2 μm. The mixture was degassed under reduced pressure while applying ultrasonic waves, and then placed in a polymerization container, the temperature of the polymerization container was maintained at 120°C, and the monomers were polymerized for 40 hours to obtain a coated rod (outer diameter 30 mm).

[0068] Using different extruders and double-layer dies connected to them, the obtained core rod and cladding rod are formed into a stacked multilayer shape of the core and the cladding, and further passed through a heating flow path for a certain period of time, thereby allowing the dopant contained in the core to diffuse into the cladding. Furthermore, XYLEXX7300CL [product name, manufactured by SABIC Innovative Plastics, polyester-modified polycarbonate] (hereinafter sometimes referred to as PC) as an outer cladding material is melted by another extruder, and a double-layer die is used to merge it with the flow path of the above-mentioned core and cladding melts, thereby forming an outer cladding at the outermost periphery. The molten resin ejected from the die is pulled to obtain an unstretched GI-type POF (preform) with a core diameter of 200μm, a cladding diameter of 280μm, and an outer diameter of 750μm.

[0069] After the obtained preform was cooled, it was stretched to 1.12 times in an oven at 80°C (Tg of the above PC - 40°C) at a stretching speed of 0.1 m / min to obtain the POF of this embodiment. The birefringence Δn of the outer coating of the obtained POF was 0.015. The obtained POF was subjected to the evaluation of (2) above. The results are shown in Table 1.

[0070] <Example 2>

[0071] POF was obtained in the same manner as in Example 1 except that the stretching ratio was changed from 1.12 times to 1.10 times. The birefringence Δn of the outer cladding portion of the obtained POF was 0.007. The obtained POF was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0072] <Example 3>

[0073] POF was obtained in the same manner as in Example 2 except that the stretching temperature was changed from 80°C to 110°C (Tg of the PC-10°C). The birefringence Δn of the outer coating portion of the obtained POF was 0.006. The obtained POF was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0074] <Example 4>

[0075] POF was obtained in the same manner as in Example 2 except that the stretching temperature was changed from 80°C to 70°C (Tg of the PC-50°C). The birefringence Δn of the outer coating portion of the obtained POF was 0.005. The obtained POF was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0076] <Example 5>

[0077] POF was obtained in the same manner as in Example 2 except that the stretching temperature was changed from 80°C to 130°C (Tg of the PC+10°C). The birefringence Δn of the outer coating portion of the obtained POF was 0.0025. The obtained POF was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0078] <Comparative Example 1>

[0079] POF was obtained in the same manner as in Example 2 except that the stretching temperature was changed from 80°C to 170°C (Tg of the PC+50°C). The birefringence Δn of the outer coating portion of the obtained POF was 0.0008. The obtained POF was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0080] <Comparative Example 2>

[0081] The preform of Example 1 was used as POF as it was (ie, not stretched). The birefringence Δn of the outer coating portion of this POF was 0.0007. This POF was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0082] <Comparative Example 3>

[0083] POF was obtained in the same manner as in Example 2 except that the stretching temperature was changed from 80°C to 140°C (Tg of the PC+20°C). The birefringence Δn of the outer coating portion of the obtained POF was 0.0015. The obtained POF was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0084] <Comparative Example 4>

[0085] An attempt was made to produce POF in the same manner as in Example 1 except that the stretching temperature was changed from 80°C to 70°C (Tg of the above PC - 50°C). However, the preform broke and POF could not be obtained.

[0086] [Table 1]

[0087]

[0088] <Evaluation>

[0089] According to the results of the examples and comparative examples, the POF of the examples of the present invention has significantly improved solvent crack resistance compared to the comparative examples. That is, the POF of the examples of the present invention does not crack even when used for a long time in a bent state (external force is applied) and in contact with a hydrocarbon solvent.

[0090] Industrial Applicability

[0091] The plastic optical fiber of the present invention is useful as a component of an optical fiber cable intended for high-speed communication. In addition, by changing the shape, it can be applied as an optical member such as a light-conducting element such as an optical waveguide, a lens for a still camera, a video camera, a telescope, glasses, a plastic contact lens, a sunlight focusing lens, a concave mirror, a polygon mirror, a prism such as a pentaprism, and the like.

[0092] Description of Reference Numerals

[0093] 10: Plastic optical fiber (POF)

[0094] 12: Core

[0095] 14: Coating

[0096] 16: Outer covering

Claims

1. A plastic optical fiber comprising: a core, a cladding arranged on the periphery of the core, and an outer cladding arranged on the periphery of the cladding, The birefringence Δn of the outer cladding portion is not less than 0.002 and not more than 0.

007.

2. The plastic optical fiber according to claim 1, wherein: The outer covering portion includes a polycarbonate-based resin.

3. The plastic optical fiber according to claim 1 or 2, wherein: After being bent at a curvature radius of 20 mm and left in contact with polyethylene glycol or a long-chain aliphatic hydrocarbon for one week, no cracks were generated.

4. A method for manufacturing a plastic optical fiber as claimed in any one of claims 1 to 3, comprising forming a preform, and stretching the preform, The stretching ratio is 1.2 times or less, and the stretching temperature is lower than the glass transition temperature of the outer covering portion.

5. A plastic optical fiber cord, comprising the plastic optical fiber according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Heat treatment of plastic optical fiber and device thereof

    JP1993011128A

  • Surface treating agent for aramid fiber, surface-treated aramid fiber, surface treatment of aramid fiber, and fiber-reinforced composite material

    JP1999335972A

  • Plastic optical fiber, optical fiber cable, optical fiber cable with plug, and manufacture of optical fiber

    JP2000147272A

  • Method for manufacturing plastic optical fiber cord

    JP2005326502A

  • Manufacturing method of plastic optical fiber, plastic optical fiber, and optical transmission body

    JP2007199420A